Transient receptor potential melastatin 2 ion channel activity in ovarian hyperstimulation syndrome physiopathology - Sanli, Cengiz; Atilgan, Remzi; Kuloglu, Tuncay; Pala, Sehmus; Turk, Bilge Aydin; Keser, Hasan Burak; Ilhan, Nevin (Tubitak Scientific & Technological Research Council Turkey, 2021)
Background/aim: Ovarian hyperstimulation syndrome (OHSS) is a complication of ovarian stimulation with increased vascular endothelial growth factor (VEGF) and vascular permeability in the ovarian tissue. Transient receptor potential melastatin 2 (TRPM2) is known to be associated with angiogenesis and vascular permeability. In this experimental study, we aimed to investigate the activity of TRPM2 in the development of OHSS. Materials and methods: Fourteen immature female rats were divided into two groups. Group 1 was the control group, and Group 2 was the OHSS group that was exposed to 10 IU of subcutaneous application of FSH for four days and 30 IU of human chorionic gonadotropin (hCG) on the 5th day. At the end of the experiment, the ovaries were removed. The right ovarian tissues were stored in 10% formol for histopathological and immunohistochemical examination. The left ovarian tissues were stored at ?80 ?C for biochemical examinations. VEGF, tumor necrosis factor-alpha (TNF??) and malondialdehyde (MDA) levels were measured in the ovarian tissue. Congestion, edema, apoptosis and TRPM2 immunoreactivity were evaluated. Results: There was a significant increase in ovarian weight in the OHSS group compared to the control group. There was a significant increase in congestion, edema, apoptosis and TRPM2 immunoreactivity in the OHSS group. A significant increase in tissue levels of VEGF, TNF?? and MDA was also found in the OHSS group compared to the control group. Conclusion: As a result of our experiment, it was found that increased TRPM2 immunoreactivity on hyperstimulated rat ovary may be the reason or result of edema and congestion. Further studies are needed to discuss our results.
Keywords: Rat; OHSS; TRPM2; VEGF; angiogenesis